Fiscal Cyclicality Under State Finances Law in Indonesia - Mirzalina Zainal; Insukindro Insukindro; Akhmad Makhfatih (Jurnal Ekonomi dan Studi Pembangunan, 2022)
This study aims to analyze the cyclicality of fiscal policy under state finances law in Indonesia. The Indonesian government officially enacted the 2003 and 2004 Laws on State Finances, and it regulates fiscal rules covering the amount of the budget deficit and balanced budget rules. This fiscal rule is expected to encourage fiscal cyclicality to become countercyclical and provide buffering to deal with various economic shocks. This study uses quarterly time-series data from 2001 to 2019. The years 2001-2004 are used as the years prior to implementing the State Finance Law. Moreover, 2005 – 2019 is the time to capture the effects of cyclicality after implementing the Law. This study uses a dynamic distributed lag model to see the effect of GDP on government spending behavior. This study indicates that fiscal cyclicality before implementing the Law on State Finance behaved acyclically. Meanwhile, after implementing the Laws, this fiscal behavior is still procyclical. It means that the fiscal rules have not been effective in changing the direction and behavior of the fiscal to be countercyclical.